Faculty Knowledge of Information Literacy Standards Has an Impact in the Classroom - Badia, Giovanna (Evidence Based Library and Information Practice, 2013)
Objective – To discover how faculty perceives information literacy and examine whether professors in different disciplines view and approach information literacy differently. Particularly, the study seeks to address the following questions: • “How do faculty members define or understand information literacy? Are they familiar with existing standards such as [those from the Association of College and Research Libraries] ACRL? Does the development of a local definition of information literacy impact faculty understanding? • How important do instructors believe information literacy to be for their students? How do they address information literacy, or expect it to be addressed within the curriculum? • Are there disciplinary differences in faculty attitudes toward and approaches to information literacy?” (p. 227) Design – Survey, i.e., an online questionnaire followed by interviews. Setting – Colleges and universities in the United States. Subjects – 834 faculty members in anthropology, the natural sciences, computer science, English literature, psychology, and political science from a sample of 50 American colleges and universities with undergraduate degree programs. Methods – An email, containing a link to a brief online survey, was sent to 834 professors from academic institutions across the United States. Three faculty members from each department in six different disciplines from each institution were contacted. The survey contained a mix of closed and open-ended questions and could be completed in less than 10 minutes. Respondents were asked to supply their contact information if they agreed to be phoned for a follow-up interview. The interview consisted of six questions that were posed to all participants, with some changes depending on the answers given. Main Results – Regardless of discipline, the majority of faculty members who responded to the survey thought that information literacy competencies were important for their students to master. The majority also rated their students as only “somewhat strong” in “identifying scholarly materials, identifying reliable/authoritative information, finding relevant information, citing sources properly, synthesizing information, and searching databases” (p. 229). Professors’ answers differed within different disciplines when it came to showing their own knowledge of information literacy standards, such as those of ACRL, and assessing the abilities of their students. For example, biology students’ web searching skills were rated higher than students in English literature and anthropology. When faculty were asked their opinions about who should be responsible for information literacy instruction, there was no straight answer. Many professors agreed that it is the responsibility of both faculty and librarians. Those faculty members who were knowledgeable about information literacy standards were also among the ones who included information literacy instruction in their courses and thought it was important for their students to learn. Conclusion – According to the author, the study results show that possibilities continue to exist for librarians to be part of information literacy endeavours, but it is still up to the librarians to start and maintain conversations with faculty on this topic. Because faculty members have not yet found systematic methods for integrating information literacy into the curriculum, they might be open to librarians’ suggestions and ideas on this topic. “Perhaps the most important finding of this study is that knowledge of and familiarity with information literacy standards is more closely associated with whether faculty address information literacy in their courses than any other variable including disciplinary area” (p. 232). Therefore, it is the librarian’s responsibility to engage in discussions with faculty about information literacy.